Selection of Amino Acid Chirality via Neutrino Interactions with (14)N in Crossed Electric and Magnetic Fields - Famiano, Michael A. (Astrobiology, 2018)
Previous work has suggested that the chirality of the amino acids could be established in the magnetic field of a nascent neutron star from a core-collapse supernova or massive collapsar. The magnetic field would orient the (14)N nuclei, and the alignment of its nuclear spin with respect to those of the electron antineutrinos emitted from the collapsing star would determine the probability of destruction of the (14)N nuclei by interactions with the antineutrinos. Subsequent work estimated the bulk polarization of the (14)N nuclei in large rotating meteoroids in such an environment. The present work adds a crucial piece of this model by describing the details by which the selective (14)N nuclear destruction would produce molecular chiral selectivity. The effects of the neutrino-induced interactions on the (14)N nuclei bound in amino acids polarized in strong magnetic fields are studied. It is shown that electric fields in the reference frame of the nuclei modify the magnetic field at the nucleus, creating nuclear magnetizations that are asymmetric in chirality. The antineutrino cross sections depend on this magnetization, creating a selective destructive effect. The environmental conditions and sites in which such a selection mechanism could occur are discussed. Selective destruction of D-enantiomers results in enantiomeric excesses which may be sufficient to drive subsequent autocatalysis necessary to produce the few-percent enantiomeric excesses found in meteorites and subsequent homochirality. Molecular quantum chemical calculations were performed for alanine, and the chirality-dependent effects studied were included. A preference for left-handed molecules was found, and enantiomeric excesses as high as 0.02% were estimated for molecules in the electromagnetic conditions expected from a core-collapse supernova. Key Words: Amino acids—Supernovae—Antineutrinos—Enantiomeric excess—Chirality. Astrobiology 18, 190–206.